UNDERSTANDING THE INDEPENDENT CURRICULUM OF ISLAMIC PRIMARY (MI) FOR PGMI STUDENT AT UNUGHA CILACAP - Ziara Aftira Zaulia; Lutfiah Hanum; Umi Zulfa; Wida Nurul Azizah (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
This research was motivated by concerns about PPL students' lack of understanding of the new curriculum which was not provided during lectures because during lectures there had not been a change to the new curriculum. Based on this, this research aims to analyze the knowledge of 3rd-semester PGMI study program students regarding the Merdeka Curriculum. This research uses a quantitative approach, with a questionnaire method and data analyzed using SPSS. The research results show that PGMI students' understanding of the Merdeka MI Curriculum is high. This condition is an important provision for those who want to become teachers.